The representation of HIV/AIDS and hepatitis B in the dentistry context - Bruno Wakayama; Clea Adas Saliba Garbin; Artenio Jose Saliba Garbin; Orlando Adas Saliba Junior; Artenio Jose Garbin (Journal of Infection in Developing Countries)
Introduction: HIV/AIDS and hepatitis B are diseases with major epidemiological and social impacts, with important effects in the dentistry context. This study aimed to compare the knowledge, presence, and manifestation of discriminatory and stigmatizing acts of dental surgeons, dental assistants, and dental students concerning social representations of HIV/AIDS and hepatitis B.